Lithium ion battery diaphragm, preparation method of lithium ion battery diaphragm and lithium ion battery using lithium ion battery diaphragm

By coating 1~6% by weight of LiOH layer on the lithium-ion battery separator, the problem of iron ion deposition during the cycle of lithium iron phosphate batteries is solved, and the internal resistance of the battery is not increased, while suppressing the dissolution and deposition of transition metals, extending the battery life and improving high-temperature cycling performance.

CN119764741AActive Publication Date: 2025-04-04BYD CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411163429.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-04-04
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

During the cycle process, iron ions depart from the positive electrode and deposited on the negative electrode, resulting in SEI film damage, capacity loss and safety hazards. Although commonly used vinyl carbonate additives can inhibit iron deposition, they will increase the internal resistance of the battery.

Method used

A lithium-ion battery separator is used, which includes a substrate layer and a coating layer. The coating layer contains 1 to 6% by weight of LiOH. By reacting LiOH with free acid in the electrolyte, acid ions are absorbed, the dissolution and deposition of transition metal ions are reduced, and active lithium ions are released under high temperature conditions.

Benefits of technology

While not increasing the internal resistance of the battery, it effectively suppresses the dissolution of transition metals and negative electrode deposition, extends the service life of the battery, improves the retention rate of high-temperature circulation capacity, and reduces dependence on vinylene carbonate additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764741A_ABST
    Figure CN119764741A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion battery diaphragm, a preparation method thereof and a lithium ion battery using the lithium ion battery diaphragm, the lithium ion battery diaphragm comprises a matrix layer and a coating layer, and the coating layer comprises LiOH; relative to the weight of the matrix layer, the coating amount of the LiOH is 1-6 wt%. The diaphragm can inhibit the dissolution of transition metal and the deposition of a negative electrode without improving the internal resistance of the battery, and avoids the use of excessive high-impedance vinylene carbonate additives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of lithium ion battery preparation, and in particular, to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery using the same. Background Art

[0002] Lithium iron phosphate batteries are gradually becoming the most mainstream power battery technology route due to their excellent safety performance, low cost and long life. It is generally believed that the olivine crystal structure of lithium iron phosphate materials is very stable and can support thousands of cycles. An obvious disadvantage of lithium iron phosphate is that iron ions will leave the positive electrode and deposit at the negative electrode during the cycle. Iron deposition will not only destroy the solid electrolyte (SEI) film of the negative electrode, causing capacity loss, but also form a short circuit point, causing safety hazards. There are two conventional methods to inhibit iron deposition in the industry. One is to bake the water inside the battery as much as possible; the other is to add a large amount of vinylene carbonate (VC) electrolyte additive to the electrolyte. VC is recognized as the most effective additive to inhibit iron deposition. It is also a consumable additive. During the cycle, the graphite of the negative electrode will expand and shrink repeatedly, and VC will be continuously consumed to form a new SEI film. In order to ensure the long cycle of lithium iron phosphate during the cycle, a large amount of VC must be added at the beginning. However, VC is easy to form a very dense SEI film at the negative electrode, resulting in a significant increase in battery impedance, which has a great impact on battery power and room temperature cycle performance. Summary of the invention

[0003] The purpose of the present disclosure is to provide a lithium ion battery separator and a preparation method thereof and a lithium ion battery using the same, wherein the separator can inhibit the dissolution of transition metals and negative electrode deposition without increasing the internal resistance of the battery, and avoid using too much high-impedance vinylene carbonate additive.

[0004] In order to achieve the above-mentioned object, the present disclosure provides a lithium-ion battery separator in a first aspect, the lithium-ion battery separator comprising a substrate layer and a coating layer, the coating layer comprising LiOH; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

[0005] Optionally, the coating amount of LiOH is 2-3 wt % relative to the weight of the base layer.

[0006] Optionally, the thickness of the substrate layer is 4-15 μm; The coating layer has a thickness of 0.5 to 5 μm; The thickness of the lithium-ion battery separator is 4.5-20 μm.

[0007] Optionally, the base layer contains one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, preferably contains one or more of polyethylene, polypropylene and polyvinylidene fluoride.

[0008] The second aspect of the present disclosure provides a method for preparing a lithium-ion battery separator, the method comprising: coating a slurry containing LiOH on a substrate layer, and then performing a drying process to form a coating layer containing LiOH on the substrate layer; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

[0009] Optionally, the drying conditions include: a time of 1 to 50 minutes and a temperature of 50 to 150°C.

[0010] Optionally, the substrate layer contains one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, preferably contains one or more of polyethylene, polypropylene and polyvinylidene fluoride; The thickness of the substrate layer is 4-15 μm; The solvent in the slurry includes one or more of water, acetone and N-methylpyrrolidone; The slurry contains a binder, which includes one or more of polyacrylic acid, styrene-butadiene rubber and polyvinylidene fluoride, and the content of the binder is 1-10% by weight; The slurry contains an auxiliary agent, which includes sodium carboxymethyl cellulose and / or polyvinyl pyrrolidone, and the content of the auxiliary agent is 1-5% by weight; The solid content of the slurry is 30-80% by weight.

[0011] A third aspect of the present disclosure provides a lithium-ion battery separator prepared by the method described in the second aspect of the present disclosure.

[0012] A fourth aspect of the present disclosure provides a lithium ion battery, the lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte, and the lithium ion battery separator according to the first aspect or the third aspect of the present disclosure; The coating layer of the lithium ion battery separator faces the positive electrode.

[0013] Optionally, the electrolyte contains vinylene carbonate; The content Y of the vinylene carbonate is 3 wt % or less, preferably 2 wt % or less, relative to the total weight of the electrolyte.

[0014] Optionally, in the lithium ion battery, in the lithium ion battery, the coating amount X of the LiOH and the content Y of the vinylene carbonate have a relationship as shown in formula (1); A=X / 2+Y formula (1) A is 2 or more, preferably 3 or more.

[0015] Optionally, the active material of the positive electrode includes a phosphate positive electrode material, preferably including one or more of lithium iron phosphate, manganese phosphate and lithium manganese iron phosphate; The active material of the negative electrode includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon-carbon composite, lithium titanate and metal elements capable of forming an alloy with lithium.

[0016] Optionally, the electrolyte contains a lithium salt and a solvent; The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate; The solvent includes an ester solvent, preferably one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate.

[0017] Through the above technical scheme, the diaphragm disclosed in the present invention has a coating layer containing a specific coating amount of LiOH, which absorbs free acid in the electrolyte on the one hand and reduces the dissolution of transition metal ions; on the other hand, the transition metal ions dissolved from the positive electrode will react with the LiOH on the diaphragm during the process of diffusing to the negative electrode through the diaphragm, which can resist the deposition of transition metal ions at the negative electrode to destroy the SEI film, while releasing active lithium ions to provide more active lithium for the battery. The use of the diaphragm disclosed in the present invention to prepare lithium-ion batteries can avoid the use of a large amount of vinylene carbonate, which leads to an increase in the internal resistance of the battery, and can also reduce the deposition of transition metals at the negative electrode, thereby increasing the service life of the lithium-ion battery and the capacity retention rate of the cycle under high temperature conditions.

[0018] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 is a scanning electron microscope image of the coating layer of the diaphragm prepared in Example 1 of the present disclosure.

[0020] Figure 2 It is a scanning electron microscope image of the coating layer of the diaphragm prepared in Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0021] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0022] A first aspect of the present disclosure provides a lithium ion battery separator, the lithium ion battery separator comprising a substrate layer and a coating layer, the coating layer comprising LiOH; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

[0023] In order to further reduce the dissolution of transition metals and negative electrode deposition, according to one embodiment of the present disclosure, the coating amount of LiOH is 2-3 wt % relative to the weight of the base layer.

[0024] In order to avoid the degradation of battery performance caused by excessive film thickness, according to one embodiment of the present disclosure, the thickness of the base layer is 4~15μm; the thickness of the coating layer is 0.5~5μm; and the thickness of the lithium-ion battery separator is 4.5~20μm.

[0025] According to one embodiment of the present disclosure, the composition of the substrate layer used is conventional in the art, for example, including one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, preferably including one or more of polyethylene, polypropylene and polyvinylidene fluoride.

[0026] The second aspect of the present disclosure provides a method for preparing a lithium-ion battery separator, wherein a slurry containing LiOH is coated on a substrate layer, and then dried to form a coating layer containing LiOH on the substrate layer; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

[0027] The method disclosed herein forms a coating layer by coating a slurry containing LiOH on a substrate layer. The method disclosed herein has simple steps and is conducive to industrial production. The prepared lithium-ion battery separator can inhibit the dissolution of transition metals and negative electrode deposition without increasing the internal resistance of the battery, significantly improve the capacity retention rate of the battery during high-temperature cycling, and avoid using too much high-impedance vinylene carbonate additives.

[0028] According to one embodiment of the present disclosure, the coating amount of LiOH is 2-3 wt % relative to the weight of the base layer.

[0029] In the present disclosure, the coating method is conventional in the art, for example, it can be blade coating, roller coating, spray coating, etc.

[0030] In order to make LiOH more evenly distributed on the base layer and avoid affecting the base layer, according to an embodiment of the present disclosure, the conditions of the drying treatment include: a time of 1 to 50 minutes and a temperature of 50 to 150°C.

[0031] According to one embodiment of the present disclosure, the base layer comprises one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, preferably comprises one or more of polyethylene, polypropylene and polyvinylidene fluoride.

[0032] According to one embodiment of the present disclosure, the thickness of the base layer is 4-15 μm.

[0033] According to one embodiment of the present disclosure, the solvent in the slurry includes one or more of water, acetone and N-methylpyrrolidone.

[0034] According to one embodiment of the present disclosure, the slurry contains a binder, and the binder includes one or more of polyacrylic acid, styrene-butadiene rubber and polyvinylidene fluoride, and the content of the binder is 1 to 10 weight %.

[0035] According to one embodiment of the present disclosure, the slurry contains an auxiliary agent, and the auxiliary agent includes one or more of sodium carboxymethyl cellulose and polyvinyl pyrrolidone, and the content of the auxiliary agent is 1-5% by weight.

[0036] According to one embodiment of the present disclosure, the solid content of the slurry is 30-80% by weight.

[0037] A third aspect of the present disclosure provides a lithium-ion battery separator prepared by the method described in the second aspect of the present disclosure.

[0038] A fourth aspect of the present disclosure provides a lithium ion battery, the lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte, and the lithium ion battery separator according to the first aspect or the third aspect of the present disclosure; The coating layer of the lithium ion battery separator faces the positive electrode.

[0039] According to one embodiment of the present disclosure, the electrolyte contains vinylene carbonate; relative to the total weight of the electrolyte, the content Y of the vinylene carbonate is less than 3 weight%, preferably less than 2 weight%; wherein, "the content of vinylene carbonate" refers to the content of vinylene carbonate in the electrolyte after battery formation; the above content can avoid the increase of internal resistance of the lithium-ion battery caused by excessive content, and can further reduce the deposition of transition metals at the negative electrode.

[0040] According to an embodiment of the present disclosure, in the lithium ion battery, the coating amount X of the LiOH and the content Y of the vinylene carbonate have a relationship as shown in formula (1); A=X / 2+Y formula (1) A is greater than 2, preferably greater than 3, for example, 3 to 6; a lithium-ion battery having the above content relationship can reduce the amount of negative electrode transition metal deposition without increasing the internal resistance of the battery, and avoid an increase in preparation cost.

[0041] According to an embodiment of the present disclosure, the active material of the positive electrode includes a phosphate positive electrode material, preferably including one or more of lithium iron phosphate, manganese phosphate and lithium manganese iron phosphate.

[0042] According to one embodiment of the present disclosure, the active material of the negative electrode includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon-carbon composites, lithium titanate, and metal elements that can form alloys with lithium.

[0043] In the present disclosure, the methods and conditions for preparing the positive electrode sheets and the negative electrode sheets are conventional in the art.

[0044] According to one embodiment of the present disclosure, the electrolyte contains a lithium salt and a solvent; the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate; the solvent includes an ester solvent, preferably including one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate.

[0045] According to one embodiment of the present disclosure, the electrolyte contains a phosphorus additive, and the phosphorus additive includes one or more of tripropynyl phosphate, tris(trimethylsilyl)phosphite and dimethyl methylphosphonate.

[0046] According to one embodiment of the present disclosure, the electrolyte contains a sulfur-based additive, and the sulfur-based additive includes one or more of methylene methanedisulfonate, vinylene sulfate, propane sultone and vinyl sulfate.

[0047] In the present disclosure, the contents of lithium salt, phosphorus-based additives, sulfur-based additives, etc. in the electrolyte are conventional in the art.

[0048] The present invention will be described in detail below by way of examples, but is not limited to the following examples.

[0049] Unless otherwise specified, the reagents used in the following examples and comparative examples are commercially available.

[0050] The thickness of substrate layer, coating layer and diaphragm is measured by micrometer.

[0051] Embodiments 1 to 11 (1) Preparation of positive electrode The active material lithium iron phosphate, the conductive agent acetylene black, the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone are fully stirred and mixed in a weight ratio of 96:2:2 to obtain a slurry with a solid content of 50 weight%, which is then coated on a current collector Al foil, dried, rolled, and die-cut to obtain a positive electrode sheet for a lithium-ion secondary battery.

[0052] (2) Preparation of negative electrode The surface-treated graphite, the conductive agent acetylene black, the adhesive styrene-butadiene rubber (SBR), the thickener sodium carbon methyl cellulose (CMC) and the solvent deionized water are fully stirred and mixed in a weight ratio of 95:2:2:1 to obtain a slurry with a solid content of 50 weight%, which is then coated on a current collector Cu foil, dried, rolled and die-cut to obtain a negative electrode sheet of a lithium-ion secondary battery.

[0053] (3) Preparation of electrolyte LiPF6 (concentration of 1 M), a certain amount of vinylene carbonate (VC) additive, and solvents of vinyl carbonate (EV) and ethyl methyl carbonate (EMC) were mixed (EC:EMC weight ratio = 30:70) to obtain an electrolyte.

[0054] (4) Preparation of diaphragm A PE film with a thickness of 12 μm (polyethylene film, surface density 7 g / m 2 ) as the base layer, a slurry (solvent: N-methylpyrrolidone, solid content: 40 wt%) containing LiOH, binder PVDF (concentration: 5 wt%) and auxiliary agent polyvinyl pyrrolidone (concentration: 3 wt%) was sprayed on the base layer and dried at 100 °C for 15 min to obtain a lithium ion battery separator. The composition and parameters are listed in Table 1.

[0055] The coating layer of the diaphragm prepared in Example 1 was tested by scanning electron microscopy, and the results were as follows: Figure 1 shown.

[0056] (5) Preparation of lithium-ion secondary batteries The positive electrode sheet, negative electrode sheet and separator prepared above are stacked, baked, injected, wetted, formed, aged, exhausted and divided to obtain a finished battery.

[0057] Comparative Examples 1 to 4 A lithium ion battery was prepared by the method of Example 1, except that LiOH was replaced by Al2O3. The relevant parameters are listed in Table 1.

[0058] The coating layer of the diaphragm prepared in Comparative Example 1 was tested by scanning electron microscopy, and the results are as follows: Figure 2 shown.

[0059] Table 1

[0060] The vinylene carbonate content Y in Table 1 above is the content of vinylene carbonate in the electrolyte after battery formation, and the testing method is gas chromatography-mass spectrometry (GC-MS).

[0061] The coating amount X in the above Table 1 indicates the coating amount of LiOH in the examples and indicates the coating amount of Al2O3 in the comparative examples.

[0062] Test Example 1: First Battery Discharge Capacity The battery formation process is to charge at 0.05C for 2 hours at 45℃, switch to 0.2C constant current and constant voltage to 3.8V (0.05C) and cut off, then discharge 1 / 3 to 2V, and measure the first battery discharge capacity.

[0063] Test Example 2 DCIR First adjust the battery to 50% SOC and get a stable voltage V1 after standing for 30 minutes; then discharge at a rate of 1.5C for 30 seconds to get a discharge voltage V2. The DCIR of the battery is defined as (V1-V2) / 1.5C.

[0064] Test Example 3 Capacity Retention Rate The lithium ion batteries prepared in the examples and comparative examples were cycled 200 times (2.0 V→3.8 V range) at a high temperature of 60° C., and the capacity retention rate was calculated.

[0065] Test Example 4 Iron deposition of negative electrode The lithium-ion battery was disassembled to obtain the negative electrode, and the iron content of the negative electrode was tested by inductively coupled plasma atomic emission spectroscopy (ICP).

[0066] The test results of test cases 1 to 4 are listed in Table 2.

[0067] Table 2

[0068] According to the above data, the diaphragm can alleviate the increase in internal resistance while inhibiting the dissolution of transition metals and negative electrode deposition. The prepared lithium-ion battery has a higher capacity retention rate, lower internal resistance and iron deposition.

[0069] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0070] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0071] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A lithium ion battery separator, characterized in that: The lithium-ion battery separator comprises a substrate layer and a coating layer, wherein the coating layer comprises LiOH; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

2. The lithium ion battery separator according to claim 1, wherein The coating amount of the LiOH is 2-3 wt % relative to the weight of the base layer.

3. The lithium ion battery separator according to claim 1, wherein The thickness of the substrate layer is 4-15 μm; The coating layer has a thickness of 0.5 to 5 μm; The thickness of the lithium-ion battery separator is 4.5-20 μm.

4. The lithium ion battery separator according to claim 1, wherein The base layer contains one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, and preferably contains one or more of polyethylene, polypropylene and polyvinylidene fluoride.

5. A method for preparing a lithium ion battery separator, characterized in that: The method comprises: coating a slurry containing LiOH on a base layer, and then performing a drying process to form a coating layer containing LiOH on the base layer; The coating amount of the LiOH is 1-6 wt % relative to the weight of the base layer.

6. The method according to claim 5, wherein: The drying conditions include: a drying time of 1 to 50 minutes and a temperature of 50 to 150°C.

7. The method according to claim 5, wherein: The substrate layer contains one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride, preferably contains one or more of polyethylene, polypropylene and polyvinylidene fluoride; The thickness of the substrate layer is 4-15 μm; The solvent in the slurry includes one or more of water, acetone and N-methylpyrrolidone; The slurry contains a binder, which includes one or more of polyacrylic acid, styrene-butadiene rubber and polyvinylidene fluoride, and the content of the binder is 1-10% by weight; The slurry contains an auxiliary agent, which includes sodium carboxymethyl cellulose and / or polyvinyl pyrrolidone, and the content of the auxiliary agent is 1-5% by weight; The solid content of the slurry is 30-80% by weight.

8. A lithium ion battery separator prepared by the method according to any one of claims 5 to 7.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte and a lithium-ion battery separator according to any one of claims 1 to 4 and 8; The coating layer of the lithium ion battery separator faces the positive electrode.

10. The lithium ion battery according to claim 9, wherein: The electrolyte contains vinylene carbonate; The content Y of the vinylene carbonate is 3 wt % or less, preferably 2 wt % or less, relative to the total weight of the electrolyte.

11. The lithium ion battery according to claim 10, wherein: In the lithium-ion battery, the coating amount X of the LiOH and the content Y of the vinylene carbonate have a relationship shown in formula (1); A=X / 2+Y formula (1) A is 2 or more, preferably 3 or more.

12. The lithium ion battery according to claim 9, wherein: The active material of the positive electrode includes a phosphate positive electrode material, preferably one or more of lithium iron phosphate, manganese phosphate and lithium manganese iron phosphate; The active material of the negative electrode includes one or more of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide, silicon-carbon composite, lithium titanate and metal elements capable of forming an alloy with lithium.

13. The lithium ion battery according to claim 9, wherein: The electrolyte contains lithium salt and solvent; The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate; The solvent includes an ester solvent, preferably one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate.

Citation Information

Patent Citations

  • Lithium secondary cell and nonaqueous electrolytic solution for use therein

    CN101292389A

  • Method for preparing lithium-supplementing composite diaphragm

    CN110571391A

  • Method for forming composite SEI film in lithium ion battery

    CN116014351A

  • Lithium-rich lithium ion battery diaphragm

    CN209515825U

  • Lithium ion secondary battery

    JP2014216061A